2019
DOI: 10.7717/peerj.8257
|View full text |Cite
|
Sign up to set email alerts
|

Sipha maydissensitivity to defences ofLolium multiflorumand its endophytic fungusEpichloëoccultans

Abstract: Background Plants possess a sophisticated immune system to defend from herbivores. These defence responses are regulated by plant hormones including salicylic acid (SA) and jasmonic acid (JA). Sometimes, plant defences can be complemented by the presence of symbiotic microorganisms. A remarkable example of this are grasses establishing symbiotic associations with Epichloë fungal endophytes. We studied the level of resistance provided by the grass’ defence hormones, and that provided by Epichloë … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…In addition, the effects of endophyte infection on SA/JA content have been reported by other studies, although their relationship with pathogen resistance was not considered. For example, Epichloë occultans significantly reduced SA concentrations but had no effect on the JA concentration in L. multiflorum (Bastías et al, 2018a(Bastías et al, , 2019. On the contrary, Ambrose et al (2015) found that Epichloë endophyte in red fescue had a null or positive effect on SA concentration, depending on the plant tissue (leaf/sheath) and the endophyte.…”
Section: Leaf Damagementioning
confidence: 98%
“…In addition, the effects of endophyte infection on SA/JA content have been reported by other studies, although their relationship with pathogen resistance was not considered. For example, Epichloë occultans significantly reduced SA concentrations but had no effect on the JA concentration in L. multiflorum (Bastías et al, 2018a(Bastías et al, , 2019. On the contrary, Ambrose et al (2015) found that Epichloë endophyte in red fescue had a null or positive effect on SA concentration, depending on the plant tissue (leaf/sheath) and the endophyte.…”
Section: Leaf Damagementioning
confidence: 98%
“…The induction of plant defence hormones can also affect Epichlo€ ederived alkaloids, and therefore the overall level of resistance of symbiotic plants. For example, increased concentrations of SA and JA hormones in L. multiflorum plants reduced the amount of Epichlo€ e-derived alkaloids within plant tissues, thereby increasing the susceptibility of symbiotic plants to insect herbivores (Bast ıas et al, 2018b(Bast ıas et al, , 2019. Likewise, Simons et al (2008) reported that the application of JA's methyl ester to endophyte-associated F. arundinacea plants lowered their resistance to aphids.…”
Section: New Phytologistmentioning
confidence: 99%
“…The (herbivory‐independent) Epichloë ‐mediated stimulation of plant growth could also constitute a mechanism of tolerance to herbivory, especially useful for those herbivores unaffected by fungal alkaloids (Gundel et al ., 2020). For example, the enhanced growth rate of L. multiflorum plants promoted by E. occultans endophytes probably contributed to compensate for the growth reduction caused by the alkaloid‐insensitive herbivore Sipha maydis (Bastías et al ., 2019).…”
Section: Ecological Benefits and Limits Of The Endophyte‐mediated Lack Of A Plant Growth–defence Trade‐offmentioning
confidence: 99%
“…Lolines were analysed using a modification of the method reported in Bastías et al (2019). Briefly, subsamples (20 mg) were extracted for 1 hr with 50 µl of 40% methanol/5% ammonia and 0.5 ml of 1,2-dichloroethane (containing 51.5 ng/ml 4-phenylmorpholine as internal standard).…”
Section: Epichloë-alkaloidsmentioning
confidence: 99%
“…In the present study, Si supply significantly reduced the induction of only one group of endophyte-alkaloids in the AR37 perennial ryegrass. Endophytic alkaloids have been shown to be an effective defence against piercing-sucking aphids (Bastías et al, 2019), for which Si defences are proven to be less effective . Thus, the nature of the interaction between Si and grass endophytes may depend on the feeding guild of the insect herbivore.…”
Section: Con Clus Ionsmentioning
confidence: 99%